Pola Asuh Orangtua Berhubungan dengan Perilaku Menstrual Hygiene pada Remaja Putri Tunagrahita di SLB Negeri 1 Bantul - Hutasoit, Masta; Sari, Ayu Putri Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Reproductive health problems are important to pay attention to in children with disabilities, especially young women, especially when they are menstruating. Lack of self-care behavior can cause infections in the reproductive organs such as vaginal discharge, urinary tract infections, and cerviks cancer. The existence of parenting and support from both parents really helps children with mental retardation to improve self-cleaning behavior independently. Parents' parenting style is needed as a guide and guide for their daughter in carrying out health care. Objective: To identify the relationship between maternal parenting style and menstrual hygiene behavior in mentally retarded young women at SLB N 1 Bantul. Methods: This study used a cross-sectional design. The population in this study were all 30 young women with mental retardation who had experienced menstruation and 30 mothers. This study uses a total sampling technique. This research was conducted at SLB N 1 Bantul, in June and July 2023. The measuring instruments used were the maternal parenting questionnaire and the menstrual hygiene behavior questionnaire. Data processing using bivariate using Spearman rank test. Results: This study obtained a correlation coefficient (r) of -0.512 and a p-value = 0.004 (p <0.05). Conclusion: There is a relationship between parenting style and adolescent menstrual hygiene behavior with mental retardation at SLB N 1 Bantul.